Impact of Corporate Governance on the Effectiveness of Companies in the Nepalese Service Sector - Devkota, Aakriti; Khatri, Anuka; Mahato, Astika; Regmi, Bina; Khatri, Dipak Kumar (Nepalese Journal of Business, 2025)
This study examines the impact of corporate governance on the effectiveness of companies in Nepalese service sector. Return on assets and operational efficiency are selected as the dependent variables. The selected independent variables are board size, board independence, board meeting, audit committee size, audit committee meeting, and company size. The study is based on secondary data of 10 commercial banks with 100 observations for the period from 2012/13 to 2021/22. The data were collected from Banking and Financial Statistics published by Nepal Rastra Bank and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of corporate governance on the effectiveness of companies in Nepalese service sector. The study showed that board size has a positive impact on return on assets and operational efficiency. It indicates that larger the board size, higher would be the return on assets and operational efficiency. Similarly, board independence has a positive impact on return on assets and operational efficiency. It indicates that increase in number of independent directors on the board leads to increase in return on assets and operational efficiency. Likewise, board meeting has a positive impact on return on assets and operational efficiency. It indicates that increase in number of board meeting leads to increase in return on assets and operational efficiency. Further, audit committee size has a positive impact on return on assets and operational efficiency. It indicates that increase in audit committee size leads to increase in return on assets and operational efficiency. In addition, audit committee meeting has a positive impact on return on assets and operational efficiency. It indicates that increase in audit committee meeting leads to increase in return on assets and operational efficiency. Likewise, company size has a positive impact on return on assets and operational efficiency. It indicates that larger the company size, higher would be the return on assets and operational efficiency.